Magnetism of FePt Nanoclusters in Polyimide. (5th May 2015) - Chipara, Mircea; George, Tom; Xu, Yingfan; Skomski, Ralph; Yue, Lanping; Ali, Nasar; Sellmyer, David J.
Abstract : FePt nanoclusters have been implanted onto polyimide films and subjected to thermal annealing in order to obtain a special magnetic phase (L10 ) dispersed within the polymer. SQUID measurements quantified the magnetic features of the as-prepared and annealed hybrid films. As-implanted FePt nanoparticles in polyimide films exhibited a blocking temperature of 70 ± 5 K. Thermal annealing in zero and 10 kOe applied magnetic field increased the magnetic anisotropy and coercivity of the samples. Wide Angle X-Ray Scattering confirmed the presence of FePt and L10 phase. All samples (as deposited and annealed) exhibited electron spin resonance spectra consisting of two overlapping lines. The broad line was a ferromagnetic resonance originating from FePt nanoparticles. Its angular dependence indicated the magnetic anisotropy of FePt nanoparticles. SEM micrographs suggest a negligible coalescence of FePt nanoparticles, supporting that the enhancement of the magnetic properties is a consequence of the improvement of the L10 structure. The narrow ESR line was assigned to nonmagnetic (paramagnetic) impurities within the samples consistent with graphite-like structures generated by the local degradation of the polymer during implantation and annealing. Raman spectroscopy confirmed the formation of graphitic structures in annealed KHN and in KHN-FePt.